Identification and Expression Analyses of Invertase Genes in Moso Bamboo Reveal Their Potential Drought Stress Functions - Zhu, Chenglei; Yang, Kebin; Li, Guangzhu; Li, Ying; Gao, Zhimin (Frontiers in Genetics, 2021)
Invertases (INVs) can irreversibly hydrolyze sucrose into fructose and glucose, which play principal roles in carbon metabolism and responses to various stresses in plants. However, little is known about the INV family in bamboos, especially their potential function in drought stress. In this study, 29 PeINVs were identified in moso bamboo (Phyllostachys edulis). They were clustered into alkaline/neutral invertase (NINV) and acid invertase (AINV) groups based on the gene structures, conserved motifs, and phylogenetic analysis results. The collinearity analysis showed nine segmental duplication pairs within PeINVs, and 25 pairs were detected between PeINVs and OsINVs. PeINVs may have undergone strong purification selection during evolution, and a variety of stress and phytohormone-related regulatory elements were found in the promoters of PeINVs. The tissue-specific expression analysis showed that PeINVs were differentially expressed in various moso bamboo tissues, which suggested that they showed functional diversity. Both the RNA-Seq and qRT-PCR results indicated that four PeINVs were significantly upregulated under drought stress. Co-expression network and Pearson’s correlation coefficient analyses showed that these PeINVs co-expressed positively with sugar and water transport genes (SWTGs), and the changes were consistent with sugar content. Overall, we speculate that the identified PeINVs are spatiotemporally expressed, which enables them to participate in moso bamboo growth and development. Furthermore, PeINVs, together with SWTGs, also seem to play vital roles in the response to drought stress. These results provide a comprehensive information resource for PeINVs, which will facilitate further study of the molecular mechanism underlying PeINVs involvement in the response to drought stress in moso bamboo.